The consonant/vowel pattern determines the structure of orthographic representations in the left fusiform gyrus. (April 2018) - Chetail, Fabienne; Ranzini, Mariagrazia; De Tiège, Xavier; Wens, Vincent; Content, Alain
Abstract: Recent findings demonstrated readers' sensitivity to the distinction between consonant and vowel letters. Especially, the way consonants and vowels are organised within written words determines their perceptual structure. The present work attempted to overcome two limitations of previous studies by examining the neurophysiological correlates of this perceptual structure through magnetoencephalography (MEG). One aim was to establish that the extraction of vowel-centred units takes place during early stages of processing. The second objective was to confirm that the vowel-centred structure pertains to the word recognition system and may constitute one level in a hierarchy of neural detectors coding orthographic strings. Participants performed a cross-case matching task in which they had to judge pairs of stimuli as identical or different. The critical manipulation concerned pairs obtained by transposing two letters, so that the vowel-centred structure was either preserved ( FOUVERT - fovuert, two vowel letter clusters) or modified ( BOUVRET - bovuret ). Mismatches were detected faster when the structure was modified. This effect was associated with a significant difference in evoked neuromagnetic fields extending from 129 to 239 msec after the stimulation. Source localization indicated a significant effect in the visual word form area around 200 msec. The results confirm the hypothesis that the vowel-centred structure is extracted during the early phases of letter string processing and that it is encoded in left fusiform regions devoted to visual word recognition.